2017
DOI: 10.1016/j.copsyc.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Child trauma exposure and psychopathology: mechanisms of risk and resilience

Abstract: Exposure to trauma in childhood is associated with elevated risk for multiple forms of psychopathology. Here we present a biopsychosocial model outlining the mechanisms that link child trauma with psychopathology and protective factors that can mitigate these risk pathways. We focus on four mechanisms of enhanced threat processing: information processing biases that facilitate rapid identification of environmental threats, disruptions in learning mechanisms underlying the acquisition of fear, heightened emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
202
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 297 publications
(227 citation statements)
references
References 51 publications
(61 reference statements)
17
202
2
6
Order By: Relevance
“…66,86 Greater amygdala reactivity to threat may result in greater emotional reactivity, or the tendency to experience frequent and intense emotional arousal and responses to environmental events, 90 and research has demonstrated a robust link between ELA and heightened emotional reactivity. 62 This association has been found across multiple measurement methods-from self-reported emotional reactivity 91 to cardiovascular responses 92,93 and amygdala reactivity. 90 Children exposed to adversity characterized by threat (e.g., abuse) are not only more emotionally reactive to facial signals of threat (e.g., expression of anger), but also show heightened amygdala reactivity to a wide range of negative and neutral stimuli, 66,94,95 indicating increased neural sensitivity to a wider range of environmental cues.…”
Section: Psychological and Behavioral Consequences Of Neural Adaptationsmentioning
confidence: 90%
See 1 more Smart Citation
“…66,86 Greater amygdala reactivity to threat may result in greater emotional reactivity, or the tendency to experience frequent and intense emotional arousal and responses to environmental events, 90 and research has demonstrated a robust link between ELA and heightened emotional reactivity. 62 This association has been found across multiple measurement methods-from self-reported emotional reactivity 91 to cardiovascular responses 92,93 and amygdala reactivity. 90 Children exposed to adversity characterized by threat (e.g., abuse) are not only more emotionally reactive to facial signals of threat (e.g., expression of anger), but also show heightened amygdala reactivity to a wide range of negative and neutral stimuli, 66,94,95 indicating increased neural sensitivity to a wider range of environmental cues.…”
Section: Psychological and Behavioral Consequences Of Neural Adaptationsmentioning
confidence: 90%
“…In threatening environments, the ability to quickly identify threats and rapidly mobilize behavioral responses that promote safety likely increases the chance of survival. 62 Thus, exposure to threatening environments, especially early in development, should lead to neural adaptations that enhance threat detection. Indeed, existing evidence suggests that children exposed to forms of ELA characterized by threat (e.g., exposure to violence) exhibit heightened neural response to signals of threat, particularly in the amygdala and other nodes of the salience network.…”
Section: Threat Detection Processesmentioning
confidence: 99%
“…Interpersonal violence may increase risk for SUD and CD through a variety of mechanisms encompassing emotional, cognitive, social, and neurobiological domains. With regard to SUD, violence exposure is associated with difficulties with emotion regulation, 46,47 which may increase risk for substance abuse either directly or indirectly if substances are used as a form of self-medication for coping with traumatic memories. 48 Interpersonal violence may also diminish response inhibition and self-regulation, particularly in emotionally salient contexts, 49 further increasing risk for substance use.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to mechanisms relevant to the onset of CD, violence exposure influences emotional and neurobiological processes involved in threat detection and salience processing, 47 and is associated with attention biases that facilitate the detection of anger, 50 social-information processing biases that increase perceptions of hostility in others, 51 heightened emotional responses to a wide range of stimuli that could signify threat, 52,53 and difficulty discriminating between threat and safety cues. 49 Each of these patterns of atypical threat detection has been linked to externalizing problems, most notably CD in the absence of callous-unemotional traits.…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 70% of children in the United States experience a Criterion A traumatic event before age 16 years (Copeland, Keeler, Angold, & Costello, ). Exposure to traumatic events in childhood is associated with elevated risk for multiple types of psychopathology (Alisic et al., ; McLaughlin & Lambert, ) and confers risk for impaired functioning across a wide variety of psychological, social, and cognitive domains (e.g., Anda et al., ; Bick & Nelson, ). A limited line of research has focused on the identification of parental‐, household‐, and community‐level risk factors associated with subsequent child exposure to trauma (Brown, Cohen, Johnson, & Salzinger, ; Chaffin, Kelleher, & Hollenberg, ), and a separate line of research has focused on developmental correlates of known prenatal risk factors (e.g., Jasinski, ; Pallitto, Campbell, & O'Campo, ; Taillieu & Brownridge, ; World Health Organization, ).…”
Section: Introductionmentioning
confidence: 99%